Polyester/clay nanocomposite synthesis via metal-free azide-alkyne click reaction - Ozdogan Tasci, Reyhan; Daglar, Ozgun; Durmaz, Hakan; Tasdelen, Mehmet Atilla (Taylor & Francis Inc, 2025)
A polyester/montmorillonite (MMT) nanocomposite is synthesized via metal-free azide-alkyne 1,3-dipolar cycloaddition (metal-free AAC) click reaction. An aliphatic polyester, poly(1,4-butane diol acetylene dicarboxylate), bearing electron-deficient alkyne groups and an azide-functionalized montmorillonite were prepared following literature procedures, then coupled at room temperature for 24 h at varied clay loadings (1, 5, and 10 wt.%) to yield the nanocomposites. Structural, thermal and morphological features of the nanocomposites are evaluated with various characterization techniques. Under nitrogen atmosphere, all nanocomposites showed enhanced thermal stability with one-step degradation, and the char yield increased by similar to 30% at the highest clay loading relative to the neat polyester. DSC revealed higher transition temperatures, with melting temperature up by similar to 3% and crystallization temperature up by similar to 11% at maximum loading, consistent with nucleation by silicate platelets. TEM and XRD evidenced mixed exfoliated and intercalated morphologies. Overall, the metal-free AAC click approach affords well-dispersed, thermally reinforced polyester/clay nanocomposites under mild, catalyst-free conditions.
Keywords: Click chemistry; metal-free azide-alkyne 1,3-dipolar cycloaddition; nanocomposite; montmorillonite; polyester